1944
DOI: 10.3181/00379727-57-14763
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapeutic Properties of Streptomycin.

Abstract: one or both gametes can be fatally injured by 20-minute exposure of the adult female to temperatures of 109"-llO"F, involving elevation of general body temperature of 5"-6"F. During the second half of the same period like treatment has no observed effect, but, as previously reported1 another period of susceptibility to heat is experienced on the 3rd day after mating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1945
1945
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…It is of particular interest to note that the two basic preparations used in this study, streptothricin and streptomycin, both of which possess similar chemical and antibacterial properties, differ greatly in their antifungal activities: the second is completely inactive, whereas the first has some definite activity against fungi. These observations thus tend to confirm those obtained by Robinson, Smith, and Graessle (1944).…”
Section: Downloaded Fromsupporting
confidence: 89%
See 1 more Smart Citation
“…It is of particular interest to note that the two basic preparations used in this study, streptothricin and streptomycin, both of which possess similar chemical and antibacterial properties, differ greatly in their antifungal activities: the second is completely inactive, whereas the first has some definite activity against fungi. These observations thus tend to confirm those obtained by Robinson, Smith, and Graessle (1944).…”
Section: Downloaded Fromsupporting
confidence: 89%
“…The marked fungistatic properties of clavacin have also been indicated Spencer, 1942, 1943). In a study of the antifungal properties of streptothricin and streptomycin, two closely related antibiotic substances produced by actinomycetes, Robinson, Smith, and Graessle (1944) demonstrated that whereas streptothricin has considerable activity against both pathogenic and saprophytic fungi, streptomycin has very little effect against these organisms.…”
mentioning
confidence: 99%
“…Streptomycin is an antibiotic that acts against Gram‐negative and Gram‐positive bacteria by binding to the 30S ribosomal subunit. At the concentration used (200 μg L −1 ), streptomycin is usually not a potent agent against fungi, requiring roughly a thousand‐fold concentration of streptomycin (3.5–8 mg mL −1 ) to be effective [ Robinson et al ., , Robinson , ]. Nystatin is mainly active against most fungi, while bacteria are not affected [ Lampen et al ., ].…”
Section: Methodsmentioning
confidence: 99%
“…, certain of the Salmonella (Robinson, Smith, and Graessle, 1944), Klebsiella pneumoniae (Donovick, Hamre, Kavanagh, and Rake, 1945), and Mycobacterium tuberculosis , as well as its in vivo therapeutic behavior against such infecting agents (Jones, Metzger, Schatz, and Waksman, 1944;Robinson, Smith, and Graessle, 1944), investigations of this antibiotic as well as of the characteristics and growth requirements of the causative organism, Streptomyces griseus, are now. being vigorously investigated in many laboratories.…”
mentioning
confidence: 99%